Butterfly Diversity on Tanjung Trees (Mimusops Elengi L.) in Community Yard Lands - Sumah, Astrid Sri Wahyuni; Kusumadinata, Ali Alamsyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Butterfly diversity depends on land type, vegetation, and human intervention in the ecosystem. This is because butterflies are very sensitive and easily affected by ecological changes and variations in plant community structure. If there is a slight change in habitat, it can cause migration or extinction of butterflies. This study aims to determine the number of butterfly species diversity that visit tanjung trees (Mimusops elengi) in community yards. This study was conducted in community land on Jalan Tanjung Rawo, Bukit Lama sub-district, Ilir Barat 1 District, Palembang City. The location of the study was determined based on the exploratory method, namely insect sampling using insect nets. Based on the results of the study 25.11 individual butterflies were obtained consisting of 8 species and 2 families (Nymphalidae and Pieridae). The Pieridae family is the number of butterfly individuals most often found as many as 8.12 individuals of Appias lyncida butterflies, and the least found is Leptosia nina (0.23 individuals) which also comes from the same family. The diversity index (1.64), and the evenness index (0.788) are included in the moderate category. In addition, 10 types of plants were also found in the community's yard that support the diversity of butterflies at that location. The number of species found in the morning, afternoon, and evening did not differ much, so that the similarity of visiting species reached 87.5%. This is related to the behavior of visiting butterfly species, also related to the morphology of flowers and hidden pollen. The results of this study are expected to provide the latest information regarding the diversity of butterflies that are active in community yards with almost the same types of plants in each community yard.